Financial Constraints and Continental Business Groups: Evidence from German Konzerns - Dorothea Schäfer; Yuriy Gorodnichenko; Oleksandr Talavera (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
Using a unique, large panel of German firms, we examine whether participation in business groups reduces the sensitivity of investment to cash flow. The main finding is that the reduction in the sensitivity is small for small firms and negligible for medium and large firms. We argue that by virtue of the continental business model, gains from business groups should be in better contract enforcement and coordination rather than in internalizing capital markets.
Keywords: G34; G32; 330; concern; business group; investment; liquidity constraints